Structure and Function of Murine αIIbβ3 (GPIIb/IIIa): Studies Using Monoclonal Antibodies and β3-null Mice - Smyth, Susan S.; Tsakiris, Dimitrios A.; Scudder, Lesley E.; Coller, Barry S. (Thrombosis and Haemostasis, 2000)
The αIIbβ3 receptor (GPIIb/IIIa) is the only platelet-specific integrin receptor and the most abundant adhesion/aggregation receptor on the surface of human platelets. Since mice are increasingly being used as models of human disease, we analyzed the structure and function of murine platelet αIIbβ3, utilizing both β3 integrin-deficient mice, who have a phenotype that resembles Glanzmann thrombasthenia, and our hamster monoclonal antibody (mAb) 1B5 to murine αIIbβ3. By immunoblot analysis, flow cytometry, and mAb binding studies, mouse platelets express abundant amounts of αIIbβ3 (60-80,000 copies/platelet). Like their human counterparts, murine αIIb and β3 exhibit different electrophoretic motilities under nonreducing (αIIb 135k Da; β3 92k Da) and reducing (αIIb 120k Da; β3 108k Da) conditions, and the αIIbβ3 complex is dissociated by EDTA at pH 8 and 37 ºC. Murine β3 is less susceptible to proteolysis by plasmin than is human β3. In addition to defective platelet aggregation, mouse platelets lacking αIIbβ3 and αVβ3 are unable to adhere to fibrinogen and prothrombin, but retain the ability to adhere to fibronectin and collagen. Following platelet activation, β3-null platelets express slightly less P-selectin than do wild-type mouse platelets. Moreover, β3-null platelets have altered tyrosine phosphorylation patterns following thrombinand collagen-induced aggregation. These results suggest fundamental similarities between human and mouse platelet activation and aggregation, but delineate subtle differences that need to be considered when comparing studies from mice and humans.
Keywords: Platelets; αIIbβ3; integrin